Tradução, adaptação cultural e validação de uma versão brasileira do questionário Smartphone Addiction Inventory (SPAI) para o rastreamento de dependência de smartphone - Julia Machado Khoury (2016)
Introduction: Smartphone Addiction is a new construct that has been increasingly studied because of its high prevalence, especially among the population of university students. The Smartphone Addiction Inventory (SPAI) was developed to assess smartphone addiction in Taiwanese university students. Objective: the purpose of this study is to translate, adapt and validate the SPAI in Brazilian university students. Method: the translation and back-translation method were employed for the adaptation of the Brazilian version of the SPAI (SPAI-BR). For the validation process the sample consisted of 415 students enrolled in undergraduate courses of the Federal University of Minas Gerais. Data collection was obtained through interviews using an electronic questionnaire consisted of socio-economic and epidemiological questions followed by the SPAI-BR and the Goodman Criteria (gold standard). The retests were carried out 10-15 days after the tests with 130 individuals. Results: the translation and cultural adaptation resulted in an instrument in Brazilian Portuguese that kept the semantic, idiomatic and conceptual equivalences from the original scale. The Confirmatory Factor Analysis (CFA) confirmed the four factors of the SPAI with the follow fit indices: x2=626.482, CFI=.938, TLI=.931, RMSE=.052 and WRMR=1.289. The Cronbach Alpha and the Kuder-Richardson Coefficient of the SPAI-BR were both of .887. The analysis of the ROC curve established a cut-off point for the SPAI-BR of nine positive answers, with a sensitivity of 79.05%, a specificity of 75.66% and an accuracy of 76.87%. Positive and negative predictive values were 64.29% and 86.70% respectively. The Spearman Correlation Coefficient between the test and the retest of the SPAI-BR was of .929 and between the SPAI-BR and the Goodman Criteria was of .750. Conclusion: this study demonstrated that the Brazilian version of the SPAI is valid and reliable for the detection of Smartphone Addiction in Brazilian university students.